THE METAPHOR OF THE GAME IN MODERN POLISH MEDIA - Skrypnyk, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the cognitive metaphor in the current Polish media. The metaphor is analyzed as a pragmatic process of creating a metaphorical phrase as a result of the words transfer from the source domain to the target domain. Based on examples excerpted from the Polish media between 2001 and 2010, the paper makes an attempt at explaining the various game`s metaphors using.